Ontologies for Knowledge modeling in construction planning Theory and application - Getuli, Vito (Ricerche. Architettura, Pianificazione, Paesaggio, Design, 2020)
Nowadays, there is an increasing recognition of the value of knowledge management in the construction projects and ontology-based semantic modelling is seen as an important means of addressing this problem, even if a knowledge-base which maps the construction planning and scheduling domains, in a formal and machine-readable way, is still missing. Addressing this issue, the book is divided in two parts. Part I, theory, is a theoretical introduction of on ontologies concepts and expert systems. Part II, application, presents a research of ontologies development for semantic modelling of construction scheduling, workspace, product and time domains. The last chapter presents the architecture of an ontology-based expert system, to show how ontologies can support automated planning mechanisms.